2019
DOI: 10.1016/j.ijcha.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atrial fibrillation on oxygen uptake and exercise tolerance in cardiovascular patients; close association with heart rate response

Abstract: To investigate the effect of atrial fibrillation (AF) on the oxygen uptake and exercise tolerance, we evaluated cardiopulmonary exercise test (CPET) data in AF patients and heart rate-matched controls with sinus rhythm (cSR) who received ambulatory cardiac rehabilitation. We compared CPET data between AF (N = 27) and cSR patients (N = 106) who had similar HRs at rest and the peak points. Oxygen uptake (VO2)/kg and relative O2 pulse (ml/bpm/kg) at rest and the anaerobic threshold (AT) level was not different be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…Right atrial contraction contributes to approximately 15-30% of the RV stroke volume; however, its contribution differs across patients with heart failure. The development of AF generally decreases the cardiac output [7], whereas the derangement of AF in cardiac output is somewhat counteracted under LVAD support. Enriquez et al have demonstrated no significant differences in peak VO 2 during a cardiopulmonary exercise test between patients with and without AF under LVAD Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Right atrial contraction contributes to approximately 15-30% of the RV stroke volume; however, its contribution differs across patients with heart failure. The development of AF generally decreases the cardiac output [7], whereas the derangement of AF in cardiac output is somewhat counteracted under LVAD support. Enriquez et al have demonstrated no significant differences in peak VO 2 during a cardiopulmonary exercise test between patients with and without AF under LVAD Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AF itself is a reason for decreased physical activity. Increased heart rate at rest causing a reduction of stroke volume and loss of atrial function can be considered to be associated with decreased physical function in patients with AF (Pardaens et al, 1997; Takano et al., 2019). Furthermore, the uncomfortable symptoms related to AF due to irregularity or tachycardia rhythm may also limit their daily activity and physical function (Nabauer et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These unfavorable symptoms can restrict physical activity and quality of life in the patients (Dorian et al., 2000). Patients with AF exhibited decreased oxygen uptake and exercise tolerance in a cardiopulmonary exercise test and treadmill test than in patients with sinus rhythm (Singh et al., 2006; Takano et al., 2019). Excessive increase in heart rate response to exercise, hemodynamical impairment of rhythm regularity, and loss of atrial contraction could be possible explanations for the lower level of physical activity in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…peak respiratory exchange ratio was over 1.1. [ 12 ] For all the subjects, expired gases were continuously measured on a breath-by-breath basis.…”
Section: Methodsmentioning
confidence: 99%